In the question above, to find the height we have to calculate the value of y.
We are going to solve the 2 equations simultaneously.
y = -0.5x² + 3x .............................................(1)
-0.5x + 2.42y = 7.65 .....................................(2)
Solve using substitution method.
From the equation 1,
y = -0.5x² + 3x
Substitute the value of y in the equation 2 with y = -0.5x² + 3x
So we have,
-0.5x + 2.42(-0.5x² + 3x ) = 7.65
-0.5x - 1.21x² + 7.26x = 7.65
- 1.21x² + 6.76x = 7.65
1.21x² - 6.76x - 7.65 = 0
This is a quadratic equation.
Solving the for x using quadratic formula.
x = (- - 6.76 +/- √( 6.76² - 4×1.21×7.65)) ÷ 2
= (6.76 +/- √82.7236) ÷2
= 6.76 +/- 9.095
x = 15.86 or -2.335
But distance can not be negative, the value of x = 15.86 ft.
The height which is the value of y will be;
y = -0.5x² + 3x
= -0.5(15.86)² + 3(15.86)
= 125.7698 + 47.58
= 173.3498 ft
Height = 173.3498 ft